The preservation of gonococci in liquid nitrogen - Ward, M. E. (1971)
Gonococci suspended in 1% proteose peptone containing 8% glycerol can be snap frozen in liquid nitrogen without detectable loss on thawing. This recovery rate has allowed the use of frozen organisms as the starting inoculum for the bulk growth of gonococci and to preserve gonococci both in urethral pus and after primary subculture for use in studies on gonococcal virulence. The method described for freezing urethral pus on charcoal swabs should make it possible to transport infected specimens from areas lacking adequate laboratory facilities.